Traços de personalidade e persistência discente em cursos de graduação na modalidade a distância - Lemos, Lívia Teixeira (2017)
This research aimed to propose guidelines for the formulation of a guide for courses coordinators in the distance modality, with the purpose of identifying the personality traits that affect student persistence behavior. To achieve the objective, the Metateoric Model of Motivation and Personality (3M Model), presented by Mowen (2000) was used. Data collection was performed through a survey with a structured questionnaire that was answered by 260 undergraduate students in the courses of the Visual Arts, Philosophy and History degree, offered in the distance modality by Universidade Federal do Espírito Santo (UFES) under the Universidade Aberta do Brasil (UAB). Statistical Package for Social Science (SPSS) was used to analyze the data using the statistical method of Multiple Linear Regression. The results showed that the 3M Model´s suitable to the investigated context and that the personality traits analyzed in a hierarchical way, from the most basic trait to the more concrete trait, contributing to explain the behavior of Student Persistence. Among the investigated situational traits, Satisfaction with the course was the most important trait that of impacted Student Persistence. The results of the research contribute to the proposal of guidelines for the formulation of a guide for the courses coordinators, aiming at the identification of personality traits that affect the persistence behavior in students of distance learning courses. The guidelines for the elaboration of the guide involve the foundations of the 3M Model adapted to the behavior of student persistence, the questionnaire to be used for data collection, and the method for the data analysis. The present research is associated with the Operations Management in the Public Sector area of the Professional Master in Public Management of UFES, because it seeks to understand the profile of the student linked to the Secretaria de Ensino a Distância (SEAD) and to propose guidelines for the formulation of a guide for coordinators of higher courses in the distance modality aiming to increase the student persistence indexes in these courses and consequently to reduce evasion